Design and Development of Dew Fan Control Device Using IoT - Diki Kurniadi; Achmad Fauzi; Arnes Sembiring (Nusantara Journal of Multidisciplinary Science, 2023)
The mist fan (blower) is an essential device in various industrial and commercial applications, particularly in cooling and ventilation processes. To increase the efficiency and user-friendliness of mist fans, we introduced an innovative design based on the Internet of Things (IoT). This project aims to create a remote-controllable mist fan controller accessible through the internet. The device will be equipped with sensors that monitor environmental temperature and humidity, allowing the mist fan to automatically adjust to maintain comfortable environmental conditions. Furthermore, the controller will include energy consumption monitoring capabilities, enabling users to optimize the mist fan's power usage. The data generated by the device will be accessible through a mobile application or web platform, allowing users to monitor and control the mist fan from anywhere and at any time. This design combines IoT technology with energy-efficient usage, thereby enhancing comfort and efficiency in various industrial and commercial applications that employ mist fans. System test result this project has the potential to positively impact energy savings and overall productivity.